Political connections and corporate dividend payout: evidence from the recent anti-corruption campaign in China - Qing, Yang (2018)
Corporate governance literature has widely recognized political forces as one of the major factors that complicate the strategic decisions of a firm. Analyzing corporate financial intermediaries can help predict and reduce the risk of information asymmetry caused by such factors. Using firm-level data from Chinese public listed companies between 2010 and 2015, this study investigates the relationship between firms’ political connections and dividend payments. We find that, after termination of political connections due to pressure from the anti-corruption campaign, firms used a reduction on their dividend payment strategy as a reaction to the political incident. Moreover, through further corporate finance research, we believe political connections influence financial leverage, which is the key factor associated with debt financing that impacts dividend payouts. We used Chinese public listed companies as our sample because China is an emerging market with a fast growing economy and is at a transition period, thus dividend payments are usually low. The complex relationship between firms and government is a natural phenomenon in emerging markets; an anti-corruption campaign is a typical political policy change that will influence such a relationship. Our findings contribute to literature in this field by using RBV (resource-based view) to demonstrate that firms will reduce dividend payments as a reaction to the termination of political connections in order to maintain a competitive advantage. We also found that anti-corruption campaigns cannot solve low dividend payouts in China. Finally, by comparing and contrasting the dividend payments among SOEs (state owned enterprises) and POEs (privately owned enterprises) before and after an anti-corruption campaign, we can contribute to literature that will help government regulators as well as firms’ make decisions about future resource allocation.